2018
DOI: 10.24156/jikk.2018.11.3.206
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Interaksi Remaja dengan Keluarga dan Teman serta Self-Esteem terhadap Perilaku Prososial Remaja Awal

Abstract: Adolescent tend to do the anti-social behavior, so it needs prevention step by developing prosocial behavior. Thisstudy aimed to analyze the effect of characteristic, family interaction, friend interaction and self-esteem onprosocial behavior among early adolescents. This research was a cross-sectional study. The location of theresearch was conducted in Junior High School X in Bogor District which was chosen purposively. The examplesof this study were 200 adolescents with same sex siblings (100 girls and 100 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…Which includes internal factors, namely interest, motivation, talent and readiness that comes from within the individual itself (Aieny et al 2020). While external factors are family factors consisting of parents' education level, family social interaction (relationships), home atmosphere, parents' economic conditions, school factors consisting of learning methods, curriculum, teacher-student relationships, student-student relationships and circumstances (Riska et al 2018). school building, while community factors consist of student activities in the community, mass media and forms of community life (Afifah 2019)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Which includes internal factors, namely interest, motivation, talent and readiness that comes from within the individual itself (Aieny et al 2020). While external factors are family factors consisting of parents' education level, family social interaction (relationships), home atmosphere, parents' economic conditions, school factors consisting of learning methods, curriculum, teacher-student relationships, student-student relationships and circumstances (Riska et al 2018). school building, while community factors consist of student activities in the community, mass media and forms of community life (Afifah 2019)…”
Section: Discussionmentioning
confidence: 99%
“…In a counseling scientific journal with the title of the relationship between social interaction skills and learning outcomes in 2012 at SMA Negeri 10 Padang obtained a number of rcount = 0.619 and rtable = 0.286 in significance level = 0.01, because the value of rcount is greater than rtable, it can be concluded that there is a significant relationship between the ability to interact socially with learning outcomes (Riska, Krisnatuti, and Yuliati 2018).…”
Section: Introductionmentioning
confidence: 96%
“…Pengetahuan ini meningkatkan kesadaran akan dampak negatif yang mungkin terjadi dan membantu remaja dalam mengambil keputusan yang bijaksana terkait gaya hidupnya (Juariah, 2021;Nugraha et al, 2021;Prihartini et al, 2002) Selain itu, pengetahuan tentang bahaya ini juga memiliki implikasi sosial yang penting. Remaja yang memahami dampak negatif dapat bertanggung jawab terhadap perilakunya sendiri dan mempertimbangkan kesejahteraan orang lain (Riska et al, 2018).…”
Section: Pembahasanunclassified